Emergency surgery for appendectomy and incidental diagnosis of superficial peritoneal endometriosis in fertile age women. Issue 4 (October 2020) - Coratti, Francesco; Vannuccini, Silvia; Foppa, Caterina; Staderini, Fabio; Coratti, Andrea; Cianchi, Fabio; Petraglia, Felice
Abstract: Research question: This study aimed to evaluate the presence of superficial peritoneal endometriosis (SUP) in women referred to emergency surgery for right iliac fossa (RIF) pain and undergoing an appendectomy, considering which factors may be useful to suspect and identify endometriosis. Design: An observational case–control study was conducted on a group ( n = 149) of fertile age women. After surgery, Group A was selected upon the diagnosis of endometriosis ( n = 34); Group B ( n = 115) represented the controls. Demographics, comorbidities and clinical findings were registered and analysed. Results: Appendicitis of various grades of severity was diagnosed in all patients, but SUP was also identified in 23%, of which 14.7% also presented with endometriosis of the appendix. Women in Group A reported chronic pelvic pain, dysmenorrhoea, dyspareunia and oral contraceptive use more frequently. At multivariate analysis, factors associated with endometriosis were: age <40 years, autoimmune disorders, multiple allergies, abdominal chronic pain, associated gynaecological pain symptoms, Alvarado score ≤6, and inconclusive ultrasound findings. Conclusions: The incidental finding of SUP in fertile age women presenting with an acute RIF pain and undergoing emergency surgery is a relevant observation. Clinical history and symptoms should guide surgeons in performing a correct diagnosis and in referring the patient to the gynaecology specialist.